Mineralogical, geochemical and radiological characterisation of Selmo Formation in Batman area, Turkey - Isik, Umit; Damla, Nevzat; Akkoca, Dicle Bal; Cevik, Ugur (Taylor & Francis Ltd, 2012)
This work deals with the mineralogical, geochemical and radiological characterisations of Selmo Formation in Batman neighbourhood. The upper Miocene-Pliocene Selmo Formation is common in the centre of Batman and composed of carbonated sandy claystones and silty-sandy stone lenses. The common whole minerals of the samples are quartz, feldspars, calcite and dolomite. The clay minerals are smectite, illite, chlorite and mixed-layer clay (chlorite-smectite). The geochemical mean values of the samples are 51.7% SiO2; 12.6% Al2O3; 6.2% Fe2O3; 3.6% MgO; 6.3% CaO; 1.1% Na2O; 1.7% K2O; 0.8% TiO2; 0.2% P2O5; 0.1% MnO; and 0.03% Cr2O3. In addition, baseline maps for the concentrations of each radionuclide, the radium equivalent activity and the outdoor gamma dose rate distributions have been plotted for the study area. The mean activity concentrations of Ra-226, Th-232, K-40 and Cs-137 were determined to be 32, 24, 210 and 9 Bq kg(-1), respectively. The assessments of the radiological hazard indices, such as radium equivalent activity, absorbed dose rate in air, annual effective dose equivalent, excess lifetime cancer risk, external hazard index and internal hazard index, were calculated and compared with the internationally accepted reference values. This study shows that the concentrations of radioactivities in the measured samples were within the recommended safety limits and did not pose to be any significant source of radiation hazard.
Keywords: geochemistry; mineralogy; natural radioactivity; radiation hazard indices; radioactive nuclides; Selmo Formation; Turkey